Rapidity and Energy Dependencies of Temperatures and Volume Extracted from Identified Charged Hadron Spectra in Proton–Proton Collisions at a Super Proton Synchrotron (SPS) - Pei-Pin Yang; Fu-Hu Liu; Khusniddin K. Olimov (Entropy, 2023)
The standard (Bose–Einstein/Fermi–Dirac, or Maxwell–Boltzmann) distribution from the relativistic ideal gas model is used to study the transverse momentum (<semantics>pT</semantics>) spectra of identified charged hadrons (<semantics>π−</semantics>, <semantics>π+</semantics>, <semantics>K−</semantics>, <semantics>K+</semantics>, <semantics><mover accent="true">p¯</mover></semantics>, and p) with different rapidities produced in inelastic proton–proton (<semantics>pp</semantics>) collisions at a Super Proton Synchrotron (SPS). The experimental data measured using the NA61/SHINE Collaboration at the center-of-mass (c.m.) energies <semantics><msqrt>s</msqrt>=6.3</semantics>, 7.7, 8.8, 12.3, and 17.3 GeV are fitted well with the distribution. It is shown that the effective temperature (<semantics>Teff</semantics> or T), kinetic freeze-out temperature (<semantics>T0</semantics>), and initial temperature (<semantics>Ti</semantics>) decrease with the increase in rapidity and increase with the increase in c.m. energy. The kinetic freeze-out volume (V) extracted from the <semantics>π−</semantics>, <semantics>π+</semantics>, <semantics>K−</semantics>, <semantics>K+</semantics>, and <semantics><mover accent="true">p¯</mover></semantics> spectra decreases with the rapidity and increase with the c.m. energy. The opposite tendency of V, extracted from the p spectra, is observed to be increasing with the rapidity and decreasing with the c.m. energy due to the effect of leading protons.